Mapping the Transition of Sustainable Entrepreneurship: From Bibliometric Analysis to Current Trends and Future Prospects - BENAYAD, Mohamed Amine; BEDOUI, Najia (Revue Internationale du Chercheur, 2025)
Abstract This article provides an in-depth bibliometric analysis of the scientific production on sustainable entrepreneurship from 2015 to 2025. Against the backdrop of climate emergencies and the transformation of economic models, the study aims to map the intellectual dynamics, dominant themes, and collaborative networks that structure this research field. Based on a dataset extracted from the Scopus database and processed using VOSviewer, various analyses were conducted: keyword co-occurrence, author co-citation, co-authorship, and lexical analysis. The results show a growing academic interest in the field, centered around consolidated thematic poles such as sustainable business models, responsible innovation, and environmental performance, along with an emerging structure of scientific communities. However, some gaps remain, notably the under-representation of Southern countries, the absence of predictive models, and limited integration of critical perspectives. The article concludes by proposing a future research agenda advocating for a more inclusive, critical, and transdisciplinary science.